Peircean Visual Semiotics for Tertiary Level Students on Storytelling of Lanna Mural Paintings at Wat Phumin, Nan Province, Thailand - Tawipas Pichaichanarong (IJCAS (International Journal of Creative and Arts Studies), 2021)
AbstractMost temples throughout Thailand have mural paintings upon their inner walls. Founder of Silpakorn University, Prof. Silpa Bhirasri, highlighted 13 temples in Thailand as having exceptional mural paintings. With its original Lanna Mural paintings, Wat Phumin in Nan is one such temple. These mural paintings depict three stories: the Buddha, the previous life of the Buddha and the ordinary lives of local people. In general, mural art is considered a medium designed to convey messages to the audience. Therefore, this study is designed to examine the capability of tertiary level students to comprehend the storytelling of the Lanna mural paintings at Wat Phumin. However, the target group of this study coincided with the data from the questionnaires which collected the data from a field trip on site, which is tertiary education. Various methodologies were used to explore the comprehension of the storytelling of Lanna mural paintings among the tertiary students via Peircean visual semiotics. As a result, the report of this research has been shown in this study. Finally, the knowledge from this study can be used to enhance teaching in various education fields related to visual semiotics and mural paintings. In addition, due to the COVID-19 Pandemic, the volume of visitors to Wat Phumin has been reduced. As the situation gets better, this study can educate anyone who plans to visit this temple. Semiotika Visual Peircean dalam Pengisahan Lukisan Mural Lanna di Wat Phumin, Provinsi Nan, Thailand pada Mahasiswa Abstrak Sebagian besar kuil di Thailand memiliki lukisan mural pada dinding bagian dalam. Pendiri Universitas Silpakorn, Prof. Silpa Bhirasri, menyoroti 13 kuil di Thailand yang memiliki lukisan mural yang luar biasa. Wat Phumin di Nan adalah salah satu kuil yang memiliki lukisan Mural Lanna Mural. Lukisan-lukisan mural ini menggambarkan tiga cerita: Sang Buddha, kehidupan Sang Buddha sebelumnya, dan kehidupan biasa masyarakat setempat. Secara umum, seni mural dianggap sebagai media yang dirancang untuk menyampaikan pesan kepada pengunjung. Oleh karena itu, penelitian ini dirancang untuk menguji kemampuan mahasiswa dalam memahami kisah pada lukisan mural Lanna yang ada di Wat Phumin. Kelompok sasaran penelitian ini berkesesuaian dengan data dari kuesioner yang didapat pada hasil kunjungan lapangan setempat, yaitu pendidikan tinggi. Berbagai metodologi digunakan untuk menggali pemahaman akan kisah pada lukisan mural Lanna di kalangan mahasiswa melalui semiotika visual Peircean. Hasilnya kemudian dilaporkan dalam penelitian ini. Pada akhirnya pengetahuan dari penelitian ini dapat digunakan untuk meningkatkan pengajaran di berbagai bidang pendidikan yang berkaitan dengan semiotika visual dan lukisan mural. Selain itu, karena pandemi COVID-19, jumlah pengunjung ke Wat Phumin menjadi berkurang. Dengan semakin membaiknya situasi, penelitian ini dapat mengedukasi siapa saja yang berencana untuk mengunjungi kuil ini.Peircean visual semiotics, tertiary level students, Lanna mural paintings, Wat Phumin | semiotika visual peircean, siswa tingkat atas, lukisan mural Lanna, Wat Phumin